Appropriating Positions in the Local Authorities – Element Strengthening the Power of System - Walczak, Waldemar (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The article presents deliberations being a continuation of conducted researches, aimed at giving the answer to a question if earlier diagnosed dysfunction in the sphere of filling positions still have their confirmation in fact. An additional components enabling thorough diagnosis analyzing phenomena were face-to-face interviews with UMŁ employees, who explicitly confirmed applied in practice mechanisms of realizing staged scripts, guaranteeing employing previously appointed candidates. Moreover, provisions of law which enable effective leading such a personnel politics were subjected to the indepth analysis, paying particular attention to the fact, that there are also offices of the civil service, which are not obliged to report information concerning recruitments to the public.In the end, the author emphasizes that issues of appropriating positions should be considered in the wider context, because in practice this actions constitute undertakings consciously implemented on purpose to enable effective taking over the control and unlimited power above the common wealth of the city by a narrow circle of local politicians, in order to ensure notable profits for the beneficiaries of created system.